2022
DOI: 10.3390/polym14152987
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Graphene-Based and Polyether-Ether-Ketone Polymers as Removable Partial Denture Esthetic Clasp Materials after Cyclic Fatigue

Abstract: The esthetic clasp material is a clinical demand for a satisfactory removable partial denture. The purpose of this study is to assess the mechanical performance of graphene-based polymer (GBP) and polyether-ether-ketone (PEEK) materials as clasp materials. Thirty-two clasps were fabricated by CAD-CAM from two materials, GBP and PEEK. All clasps were tested for retention force after 10,000 cycles of insertion and removal and thermocycling. The clasp arms’ deformation was measured, and areas of stress–strain con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It is a PMMA polymer enhanced by graphene nanomaterial with an elastic modulus (3.2 GPa). 17,24 This value is close to polymers used for a such application as PEEK (3.0-5.5 GPa) and far beyond alloys such as Cr-Co (200 GPa), which allows reduced clasp thickness and width. 1,26,[31][32][33] However, the material has the required flexibility to act as clasp material but is not rigid enough to be shaped in small and thin sections.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…It is a PMMA polymer enhanced by graphene nanomaterial with an elastic modulus (3.2 GPa). 17,24 This value is close to polymers used for a such application as PEEK (3.0-5.5 GPa) and far beyond alloys such as Cr-Co (200 GPa), which allows reduced clasp thickness and width. 1,26,[31][32][33] However, the material has the required flexibility to act as clasp material but is not rigid enough to be shaped in small and thin sections.…”
Section: Discussionmentioning
confidence: 57%
“…38,39 Previous studies showed higher stress values at the connection between the retentive clasp arm and the guiding plane, rendering it more prone to fracture. 1,24,26,38 Thus, keeping larger dimensions in that area is wise to endure stress concentrations. Although adequate tapering of the clasp tips is mandatory for metallic clasps because of their high rigidity, higher flexibility renders polymer clasps acceptable in less tapering values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also allows for a comparison of any permanent distortion of the clasps following prolonged cyclic testing, which would be expected to have a detrimental effect on clasp retention [ 72 ]. Hussein [ 73 ] evaluated the retentive force after cyclic aging and the pull-off force of removable partial denture clasps manufactured from PEEK and GBP (graphene-based polymer) materials. The analog tooth material selected was CoCr material.…”
Section: Characteristics Of Peek and Its Composite Materialsmentioning
confidence: 99%